Temporal Substitution and the Recreational Value of Coastal Amenities - Smith, V. Kerry; Palmquist, Raymond B. (The Review of Economics and Statistics, 1994)
This paper proposes a method for measuring the effects of substitutions in the timing of recreational use on people's willingness to pay for nonmarketed resources. Using the three markets (peak, pre-peak, and post-peak) for weekly rentals of vacation properties along the Outer Banks of North Carolina, we are able to control for changes in the mix of site characteristics selected at different times and estimate the effects of temporal substitution on tradeoffs between other characteristics. Proximity to the ocean was found to be a significant determinant of temporal substitution between the peak and pre-peak seasons with ocean front properties having 1.9 percent to 4.7 percent smaller discounts for preseason rentals relative to other properties. Copyright 1994 by MIT Press.